826. HIV Infection and HPV Genotype Patterns among Young Women with Advanced Cervical Neoplasia in Davidson County, Tennessee. (4th December 2021) - Giffin, Leahanne; Zhu, Yuwei; Pemmaraju, Manideepthi; Blankenship, Sheelah; Sackey, Emmanuel; Querec, Troy; Unger, Elizabeth R; Cleveland, Angela; Gargano, Julia; Castilho, Jessica L
Abstract: Background: Women living with HIV (WLWH) experience high rates of human papillomavirus (HPV) infection and increased risk of cervical cancer. High-risk HPV (HR-HPV) types 16/18 cause most cervical precancers and cancers in women with and without HIV. However, contributions of other HR-HPV types to cervical disease among WLWH are not fully understood. We compared CIN2+ cases (cervical intraepithelial neoplasia grade 2 or higher or adenocarcinoma in situ) and the association between non-16/18 HPV types among women with and without HIV. Methods: Davidson County, Tennessee, women aged 18-39 years with CIN2+ diagnosed between 2008-2016 with HPV genotyping were included. HIV status, demographics, and histology were abstracted from medical records. Neighborhood-level socioeconomic factors were derived from Integrated Public Use Microdata Series. Archived cervical tissue was tested for 37 HPV types to define CIN2+ cases negative for HPV 16/18, regardless of presence of other HR-HPV strains. Characteristics of women with CIN2+ and HPV typing patterns were compared between women with and without HIV using Wilcoxon and Chi-square tests. Logistic regression assessed the association of non-16/18 HPV types and HIV infection, adjusting for age, race, calendar year, insurance, HPV vaccination, and neighborhood socioeconomic factors (selected a priori). Results: Among 2, 116 women included, 1, 093 (52%) had neither HPV16 nor HPV18. Compared to women without HIV, the 27 WLWH included were more likely to be >30 years of age, Black race, and live in neighborhoods with higher measures of poverty (Table 1). HPV types did not statistically differ by HIV status, though WLWH had a higher number of HR-HPV types present (Table 2). HIV infection was not significantly associated with non-16/18 HPV type after adjusting for confounders (adjusted OR 0.86 [95%CI: 0.4-1.88]). Conclusion: Among women with CIN2+, HIV infection was not significantly associated with non-16/18 HPV types. However, WLWH had a higher number of high-risk HPV types detected. Our study was limited by the small number of WLWH included. Disclosures: All Authors : No reported disclosures